Utilization of food waste as edible coatings to support a circular economy: a systematic literature review - Elya Antariksana Bachmida; Nur Afni; Wiharyani Werdiningsih (Journal of Food and Agricultural Product, 2026)
Food waste represents a global challenge that significantly affects environmental sustainability and the resilience of food systems. Innovative approach to food waste valorization involves its conversion into edible coating materials to extend the shelf life of food products. This study aims to systematically examine the potential of various food waste streams as raw materials for edible coatings in support of circular economy implementation. A systematic literature review (SLR) methodology was employed by identifying 15 relevant research articles published between 2010- 2025 through Google Scholar. The findings indicate that organic residues such as fruit peels (banana, cocoa, jackfruit), starchy wastes (banana pseudostem, durian seeds, potato peels, cassava), and animal-derived waste (crustacean shells) contain essential biopolymers, including pectin, starch, and chitosan. Data synthesis further reveals that the application of modern extraction techniques, such as Microwave-Assisted Extraction (MAE), along with composite formulations enriched with active agents (liquid smoke, herbal extracts, or beeswax), significantly enhances the mechanical and hydrophobic properties of the coatings. Applications on climacteric fruits (tomato, papaya, citrus) and non-climacteric fruits (strawberry, grape, apple) have been shown to effectively reduce respiration and transpiration rates, leading to decreased weight loss and improved vitamin C retention. In animal-based products (fish and sausages), chitosan coatings demonstrated the ability to inhibit lipid oxidation and suppress microbial growth, as indicated by Total Plate Count (TPC) values. Overall, the transformation of food waste into edible coatings not only provides protection against chemical and microbiological deterioration but also generates economic value from organic residues while mitigating environmental impacts. Keywords: Edible coating, food waste, circular economy, shelf life, biopolymer